The fourth industrial revolution and the future of manufacturing work in Australia: challenges and opportunities. (3rd July 2018) - Dean, Mark; Spoehr, John
ABSTRACT: Many now argue that we are at the beginning of a 'fourth industrial revolution' (Industry 4.0) – a time characterised by the convergence of a wide range of mutually reinforcing digital technologies accompanied by great advances in computing power and the ability to network things relatively cheaply. In the Australian context little attention is paid to the implications of the Industry 4.0 for workplaces, workers and society through technology-driven changes. This paper addresses these under-researched dimensions of the debate in Australia, focusing attention on the potential for particular variants of Industry 4.0 to be vehicles for adoption of regressive 'business models' that accelerate the growth of precarious, unsafe and alienating forms of employment in the manufacturing sector. We also examine a more optimistic possible outcome by asking how Industry 4.0 might serve as a vehicle for reversing deindustrialisation in Australia, and we present a research agenda to begin working towards this. An industrial relations system equipped for the digital age must be capable of preventing the growth of precarious, exploitative and alienating forms of employment that undermine long held legal, ethical and community standards.